(untitled) (Bangladesh Journal of Anatomy, 2010)
Context: The parathyroid gland, the last major organ to be recognized in humans, is an essential endocrine gland. The hormone secreted by the parathyroid gland provides a powerful mechanism for controlling extracellular calcium and phosphate concentrations. Knowledge of location and number of parathyroid gland is essential to surgeon, endocrinologist, sonologist and pathologist for better diagnosis and management of parathyroid diseases. Study design: A descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from January 2008 to December 2008. Materials: The present study was performed on post mortem parathyroid glands of 60 Bangladeshi people in different age groups. Total 207 parathyroid glands were taken from this 60 cadavers. The samples were collected from the unclaimed dead bodies within 24 hours after death that were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. Methods: The samples were divided into three different age groups ranging from 15 to 75 years. The three groups are group A (10-30 years), group B (31-60 years) and group C (61-90 years). All samples were studied morphologically. Results: In the present study of 60 cadavers, 207 parathyroid glands were identified in relation to posterior border of thyroid lobe. And most of the superior parathyroid glands were found on the middle third of the posterior border of the thyroid lobe and most of the inferior parathyroid glands were found on the lower third of the posterior border of the thyroid lobe. In this study the highest number of parathyroid glands per person was four, found in about 63.333% of cases and lowest was one, found in 5% of cases, two parathyroid glands were found in 8.33% of cases and three parathyroid glands were found in 23.33% of cases. The average number of parathyroid glands per person was 3.45. Conclusion: The parathyroid glands vary in number and location. Key words: Location; number; parathyroid gland. DOI: 10.3329/bja.v7i2.6086 Bangladesh J. Anat. 2009; 7(2) : 73-79